2021
DOI: 10.1038/s41467-021-24913-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive hydrodynamic imaging in plant roots at cellular resolution

Abstract: A key impediment to studying water-related mechanisms in plants is the inability to non-invasively image water fluxes in cells at high temporal and spatial resolution. Here, we report that Raman microspectroscopy, complemented by hydrodynamic modelling, can achieve this goal - monitoring hydrodynamics within living root tissues at cell- and sub-second-scale resolutions. Raman imaging of water-transporting xylem vessels in Arabidopsis thaliana mutant roots reveals faster xylem water transport in endodermal diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 43 publications
(64 reference statements)
0
19
0
Order By: Relevance
“…Our major concern was to understand the relative impact of elementary axial and radial hydraulic parameters on sap flow. Whereas confrontation of theoretical and experimental data through model sensitivity analysis remains the most common approach, there is a restricted number of studies whereby hydraulic parameters were deduced from inverse modeling and integration of architectural components ( Doussan et al, 1998b , 2006 ; Zarebanadkouki et al, 2016; Meunier et al, 2018 ; Pascut et al, 2021 ;). While these earlier studies relied on functional analyses of individual axial roots of maize, lupine or Arabidopsis, we describe here a procedure based on cut-and-flow measurements for simultaneous determination of axial and radial conductance in highly branched root systems.…”
Section: Discussionmentioning
confidence: 99%
“…Our major concern was to understand the relative impact of elementary axial and radial hydraulic parameters on sap flow. Whereas confrontation of theoretical and experimental data through model sensitivity analysis remains the most common approach, there is a restricted number of studies whereby hydraulic parameters were deduced from inverse modeling and integration of architectural components ( Doussan et al, 1998b , 2006 ; Zarebanadkouki et al, 2016; Meunier et al, 2018 ; Pascut et al, 2021 ;). While these earlier studies relied on functional analyses of individual axial roots of maize, lupine or Arabidopsis, we describe here a procedure based on cut-and-flow measurements for simultaneous determination of axial and radial conductance in highly branched root systems.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that besides a dominant apoplastic transport across the rhizodermis and cortex, the contribution of the hydraulic conductance of the cell‐to‐cell path to the overall conductance increased significantly from the first layer of the cortex toward the inner layers from 2% to 23%. At the endodermal diffusion barrier, there is increasing evidence that purely apoplastic water transport is excluded (Knipfer & Fricke, 2010; Pascut et al, 2021) while endodermal cell membrane aquaporins largely mediate cell‐to‐cell water flow (Maurel, 1997; Tyerman et al, 1999) and would control up to 70% of the radial conductance prior to suberisation (Couvreur et al, 2018). However, the analysis of cell‐scale factors controlling root radial conductance is complicated by the fact that the conductance of the multiple composite paths vary radially (Ding et al, 2020) and longitudinally with the maturation of diffusion barriers (Hachez et al, 2006; Wang et al, 2019), and depend on the root direct environment and anatomy (Bramley et al, 2009; Heymans et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that besides a dominant apoplastic transport across the rhizodermis and cortex, the contribution of the hydraulic conductance of the cell-to-cell path to the overall conductance increased significantly from the first layer of the cortex toward the inner layers from 2% to 23%. At the endodermal diffusion barrier, there is increasing evidence that purely apoplastic water transport is excluded (Knipfer & Fricke, 2010;Pascut et al, 2021) while endodermal cell membrane aquaporins largely mediate cell-to-cell water flow (Maurel, 1997;Tyerman et al, 1999) and would control up to 70% of the radial conductance prior to suberisation (Couvreur et al, 2018). Asterisks denote statistically significant differences between treatments by Student's t test (P <0.05)…”
Section: Short Term Hn Treatment Induces Genotypedependent Changes In...mentioning
confidence: 99%
“…Mathematical modelling is a powerful tool to better understand roots and rhizosphere processes and to help us identify optimal root phenotypes in contrasting environments (Roose et al ., 2016; Postma et al ., 2017; Pascut et al ., 2021). Functional-structural root architecture models are particularly well suited for such endeavour (Dunbabin et al ., 2013; Landl et al ., 2021).…”
Section: Plant Modelling: An Underused Approach To Root Phenotyping?mentioning
confidence: 99%